Description of a new scorpionfish (Scorpaenoidei, Sebastolobinae) from the tropical eastern Pacific - Béarez, Philippe; Motomura, Hiroyuki (Zootaxa, 2009)
A new spiny scorpionfish, Trachyscorpia verai, is described from a single specimen caught by deepwater longline off Puerto López (Ecuador, Tropical Eastern Pacific). This scorpionfish is distinguished from all other species of Trachyscorpia by a unique combination of characters: dorsal-fin spines 12, vertebrae 26, and gas bladder absent. Other diagnostic characters are: maxilla unscaled, third dorsal spine long, and pelvic spine short. This is the second species of Trachyscorpia known from the TEP and the sixth worldwide.